Integrality in the approach to digital inclusion - Castro Obando, Valeria (2021)
The following article presents the concept of digital inclusion from a critical perspective in which it is considered as a complex and multidimensional term, which embodies a process that seeks to enhance the use of Information and Communication Technologies (ICT) and develop a series of practices, abilities and skills in order to produce a technological appropriation that provides adequate and sufficient capacities to survive in the Information and Knowledge Society (IKS). Such an approach comprises three different areas of action: access to ICTs (equipment and development of telecommunications infrastructure), digital literacy and digital appropriation (use of ICTs and reinvention and adaptation of uses). Such a vision of digital inclusion requires the implementation of integral solutions that abandon the reductionist and one-dimensional views of this public problem, adopting strategies that combine actions that include investmentand development of telecommunications infrastructure, and the equipping and affordability of technologies, quality of services and the creation of capacities for appropriation and digital literacy, as well as considering the differentiated needs of those sectors in the greatest condition of vulnerability.